A Bottom-up Look at Mutual Trust and the Legal Practice of the Aranyosi Test - Peristeridou, Christina (Review of European and Comparative Law, 2023)
This contribution offers an insight into the legal practice of the Aranyosi test during the EAW proceedings in seven Member States, an outcome of the research conducted during the ImprovEAW Project. Only the executing judicial authorities of some Member States do trigger the test. Member States are roughly differentiated between those having facilities with usually bad or usually good detention conditions, promoting antagonistic relationships instead of equal partnership. The lack of streamlining of the communication when supplementary information is requested, the lack of common standards and approach towards guarantees lead to further misunderstandings and frustration. The findings of this research have revealed the importance of departing from a pure legal understanding of mutual trust and follow a more empirical, experiential or bottom-up concept. Mutual trust is not only a legal concept, but it underpins the legal culture of the cooperation and collegial attitudes of authorities towards one another. This expression of mutual trust remains quite undiscovered: how is miscommunication affecting mutual trust? Do judicial authorities of legal systems express collegiality to one another? How do cultural aspects and preconceived ideas regarding the quality of other legal systems influence mutual trust? Accordingly, some suggestions have been made to improve the cooperation and the establishment of rapport when supplementary information is requested. Finally, I advocate for a more neutral view towards the Aranyosi test. As opposed to considering it as a supervisory mechanism, I have explored the idea of approaching it as a risk management tool: it tackles risks created by mutual trust. Such approach helps both sides to take responsibility to avert ad hoc risks, instead of experiencing Aranyosi as a testing moment. Such approach centres the real problem, i.e. the risks created by mutual trust for individuals and it can stimulate more proactive policy-making in this regard.